Alteration of Intestinal Microbiota in 3-Deoxyglucosone-Induced Prediabetic Rats. (25th August 2020) - Cai, Jin; Zhou, Liang; Song, Xiudao; Yin, Meiqi; Liang, Guoqiang; Xu, Heng; Zhang, Lurong; Jiang, Guorong; Huang, Fei
Abstract : Our previous research suggests that 3-deoxyglucosone (3DG), formed in the caramelization course and Maillard reactions in food, is an independent factor for the development of prediabetes. Since the relationship between type 2 diabetes (T2D) and intestinal microbiota is moving from correlation to causality, we investigated the alterations in the composition and function of the intestinal microbiota in 3DG-induced prediabetic rats. Rats were given 50 mg/kg 3DG by intragastric administration for two weeks. Microbial profiling in faeces samples was determined through the 16S rRNA gene sequence. The glucagon-like peptide 2 (GLP-2) and lipopolysaccharide (LPS) levels in plasma and intestinal tissues were measured by ELISA and Limulus test, respectively. 3DG treatment did not significantly change the richness and evenness but affected the composition of intestinal microbiota. At the phylum level, 3DG treatment increased the abundance of nondominant bacteria Proteobacteria but did not cause the change of the dominant bacteria. Meanwhile, the abundance of the Prevotellaceae family and Parasutterela genus and the Alcaligencaeae family and Burkholderiales order and its attachment to the Betaproteobacteria class were overrepresented in the 3DG group. The bacteria of Candidatus Soleaferrea genus, Gelria genus, and Thermoanaerobacteraceae family and its attachment to Thermoanaerobacterales order were apparently more abundant in the control group. In addition, 45 KEGG pathways were altered after two-week intragastric administration of 3DG. Among these KEGG pathways, 13 KEGG pathways were involved in host metabolic function related to amino acid metabolism, carbohydrate metabolism, metabolism of cofactors and vitamins, and metabolism of terpenoids and polyketides. Moreover, the increased LPS levels and the decreased GLP-2 concentration in plasma and intestinal tissues were observed in 3DG-treated rats, together with the impaired fasting glucose and oral glucose tolerance. The alterations in composition and function of the intestinal microbiota were observed in 3DG-treated rats, which provides a possible mechanism linking exogenous 3DG intake to the development of prediabetes.